PENGUNGKAPAN IDENTITAS ANAK YANG BERHADAPAN DENGAN HUKUM OLEH PERS: EVALUASI TERHADAP DEWAN PERS INDONESIA - Hasanah, Nur; Rinwigati, Patricia (UNES Law Review, 2023)
This article examines the disclosure of the identity of Children in Conflict with the Law (CCL) by the press in reporting on the internet media. The research method used is normative juridical with a prescriptive research type that is literature study. The type of data used is secondary data. The research results show that the disclosure of identities by the press has violated the provisions of Article 5 of the Journalistic Code of Ethics and the Regulation of the Press Council Number 1/PERATURAN-DP/II/2019. The disclosure of photographs in such cases can be reported to the Press Council by filing a complaint against the journalistic work. The concealment of the identity of children in conflict with the law aims to ensure that CCL can be accepted in society, as if the identity of CCL is revealed, there is a fear that the child will have difficulty being accepted by society, as they may be labeled as "criminal perpetrators."